Effects of agricultural management on greenhouse gas emissions, carbon and nitrogen sequestration, and DAYCENT simulation accuracy - Toonsiri, Phasita, author; Davis, Jessica G., advisor; Cotrufo, M. Francesca, committee member; Conant, Richard T., committee member; Del Grosso, Stephen J., committee member (Colorado State University. Libraries, 2017)
Agricultural activities affect greenhouse gases (GHGs) sources and sinks in terrestrial ecosystems. Organic fertilizer provides nitrogen (N) and organic carbon (C) to soil, resulting in enhanced N and C substrates for nitrification and denitrification which produce nitrous oxide (N2O) and for heterotrophic activity which generates carbon dioxide (CO2). Therefore, reduction of N and C substrates for N2O and CO2 production can reduce these emissions. Proper organic fertilizer application can regulate or reduce the loss of N2O from soil. In addition to reducing GHG production, increasing the potential of soil to sequester soil organic matter (SOM) is a key strategy for mitigating GHG emissions. Increasing organic inputs and reducing SOM turnover rate are keys for this mitigation. The persistence of SOM in agricultural soils is largely associated with the level of protection of C in stable aggregates. Therefore, applying proper practices to increase the stable aggregates can decrease the SOM decay rate, resulting in reduced loss of GHGs such as N2O and CO2 from soil. The focus of my dissertation is the study of (i) N2O and CO2 emissions from a lettuce field which received different organic fertilizer applications, (ii) SOM persistence and stable aggregates in organic and conventional farming systems, and (iii) simulation of N2O and CO2 emissions in organic lettuce using the DAYCENT model. The first study was performed in the summers of 2013 and 2014 at the Colorado State University Horticulture Research Center in Fort Collins, CO to determine the effects of environmental factors and four organic fertilizers (feather meal, blood meal, fish emulsion, and cyano-fertilizer) applied at different rates (0, 28, 56, and 112 kg N ha-1) on N2O and CO2 emissions from a lettuce field (Lactuca sativa L.). Feather meal and blood meal were applied at the full rate (single application) prior to transplanting lettuce, and fish emulsion and cyano-fertilizer were applied five times (multiple applications) after transplanting. The results showed that single application treatments significantly increased cumulative N2O emissions as compared with control, but multiple application treatments did not. However, single application treatments could be overestimated due to chamber placement over fertilizer bands. Cumulative CO2 emissions from single application and multiple application treatments in 2013 were not different, while in 2014, single application treatments presented higher CO2 emissions than multiple application treatments. The second study evaluated the effect of management on aggregate stability and SOM protection and persistence. The study was conducted by collecting soil samples from conventional and organic vegetable fields in different locations (California, Colorado, and New York) and at different soil depths (0-10, 10-20, and 20-30 cm) and analyzing their properties, microbial biomass, and aggregate size distribution. The results showed that organic farming systems have more microbial biomass, thus resulting in enhanced aggregate stability and the formation of organo-mineral bonding of microbial products, thereby storing higher C and N stocks than conventional farming systems. The last study compared N2O and CO2 emissions from field measurements with DAYCENT simulation. The data from the first study in 2014 was used to test the DAYCENT model. The result showed that DAYCENT simulated N2O and CO2 emissions from feather meal and blood meal (single application) better than for fish emulsion and cyano-fertilizer (multiple applications). In addition, the DAYCENT model had low potential to simulate soil water content and soil temperature in irrigated organic lettuce. Overall, the results of these studies show (i) multiple applications of cyano-fertilizer reduced N2O and CO2 emissions while maintaining lettuce yields, (ii) organic farming practices resulted in higher C inputs, microbial biomass, aggregate stability, and protected SOM relative to conventional farming practices, and (iii) DAYCENT reasonably simulated N2O and CO2 emissions from an irrigated organic lettuce field receiving solid organic fertilizers in single applications. These results should be used to support agricultural management decisions.